A critical review of Kant thoughts on ethical education: a reflection on current era - Gohar, Amna [UNESP]; de Carvalho, Alonso Bezerra [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2023)
Education has many aspects to be experienced that need to be learned by students, where the most important and philosophically considered necessary is ethical experiences. In the current era ethical education is considered significant for students to teach them positivity and to reduce ethical crises from their life. In this study Kant thoughts on ethics and education were discussed in order to explore its importance. In which the imperative role of Kant thoughts was debated for the current education. His thoughts have had great influence on western philosophy and earned the chief position for ethics till date. According to Kant the central part of education is ethical and its main ambition is formatting one's inner discipline. Also, he said that it has a strong relation between ethics and education. Hence, Kant's thoughts are appreciated in this era therefore ethics is suitable to implement in the education system to acquire better results.
Una revisión crítica del pensamiento kantiano sobre la educación ética: una reflexión sobre la época actual
Uma revisão crítica do pensamento de Kant sobre a educação ética: uma reflexão sobre a era atual
Keywords: Education; Ethics; Kant thoughts